Improving the Electrical Parameters of a Photovoltaic Panel by Means of an Induced or Forced Air Stream. (30th March 2013) - Mazón-Hernández, R.; García-Cascales, J. R.; Vera-García, F.; Káiser, A. S.; Zamora, B.
Abstract : The main priority in photovoltaic (PV) panels is the production of electricity. The transformation of solar energy into electricity depends on the operating temperature in such a way that the performance increases with the decreasing temperatures. In the existing literature, different cooling techniques can be found. The purpose of most of them is to use air or water as thermal energy carriers. This work is focused on the use of air as a working fluid whose movement is either induced by natural convection or forced by means of a fan. The aim of this study is to characterise the electrical behaviour of the solar panels in order to improve the design of photovoltaic installations placed in roof applications ensuring low operating temperatures which will correct and reverse the effects produced on efficiency by high temperature. To do this, a test installation has been constructed at the Universidad Politécnica de Cartagena in Spain. In this paper, the results of the tests carried out on two identical solar panels are included. One of them has been modified and mounted on different channels through which air flows. The different studies conducted show the effects of the air channel cross-section, the air velocity, and the panel temperature on the electrical parameters of the solar panels, such as the voltage, current, power, and performance. The results conclude that the air space between the photovoltaic panels and a steel roof must be high enough to allow the panel to be cooled and consequently to achieve higher efficiency.